Effect of Hibiscus sabdariffa (Roselle) supplementation in regulating blood lipids among patients with metabolic syndrome and related disorders: A systematic review and meta‐analysis. (12th December 2019) - Zhang, Boxun; Yue, Rensong; Wang, Ying; Wang, Lizhen; Chin, Jiawei; Huang, Xiaoying; Jiang, Yayi
Abstract : This study aimed to assess the efficacy of Hibiscus sabdariffa (Roselle) in regulating blood lipids among patients with metabolic syndrome and related disorders. PubMed, the Cochrane Library, Embase, Web of Science, and Clinical Trials were searched to identify the randomised controlled trials meeting the inclusion criteria. Study selection, data extraction, and risk assessment were performed according to Cochrane handbook; available data were analysed using STATA 15.0 software. Eventually, nine trials involving 503 participants were included in this meta‐analysis. The results showed that compared with the control group, H. sabdariffa supplementation could reduce total cholesterol (WMD = −14.66; 95% CI [−18.22, −11.10]; p = .000; I 2 = 46.9%) and low‐density lipoprotein cholesterol (WMD = −9.46; 95% CI [−14.93, −3.99]; p = .001; I 2 = 50.1%) but could not effectively reduce triglyceride (WMD = −0.77; 95% CI [−7.87, 6.33]; p = 0.832; I 2 = 0%). Meanwhile, there were no serious adverse reactions reported in the included studies. To summarise, current evidence suggests that the benefits of H. sabdariffa supplementation to patients with metabolic diseases are associated with its cholesterol‐lowering effects; however, more high‐quality clinical trials are needed to confirm these results.